Factors affecting coaching transfer at a South African State-Owned Entity - Kola, Mantiti (My University, 2021)
The use of coaching as a human capital tool to improve productivity and performance is on the rise. A consequence of this increased application is the demand for empirical data to understand the process and conditions by which it operates and its efficacy in achieving predetermined goals. The purpose of the study was to establish organisational factors and coachee attributes that promote or hinder coaching transfer into the workplace. This study used a qualitative research design to collect information in one of the South African State Owned Entity (SOE), where 15 management and human resources members were interviewed. The findings of the study revealed that there were work environment characteristics and specific coachee attributes that promoted and those that derail the coaching transfer. By identifying the importance of work environment and coachee attributes as pivotal in promoting coaching transfer at the SOE, the research may assist in improving future coaching programmes to alleviate the barriers hindering positive coaching transfer. More importantly, the study developed a conceptual framework to help guide the coaching transfer in the organisation, and other SOEs could adapt this conceptual framework
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Business and Executive Coaching), 2021
Keywords: Coaching transfer; State Owned-Entity; Work environment factors; Coachee attributes; SDG-8: Decent work and economic growth